2022
DOI: 10.31234/osf.io/vghw8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TANGO: A reliable, open-source, browser-based task to assess individual differences in gaze understanding in 3 to 5-year-old children and adults

Abstract: Traditional measures of social cognition used in developmental research often lack satisfactory psychometric properties and are not designed to capture variation between individuals. Here we present TANGO (Task for Assessing iNdividual differences in Gaze understanding - Open); a brief (approx. 5–10min), reliable, open-source task to quantify individual differences in the understanding of gaze cues. Our interactive browser-based task works across devices and enables in-person and remote testing. The implemente… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
3
6
0
Order By: Relevance
“…We found that 18‐ to 27‐month‐olds’ goal‐based action predictions—reflected in above‐chance looking toward the location that matches the outcome of an agent's action goal—occurred in our remotely tested sample, replicating results obtained with in‐lab commercial eye‐tracking systems (Schuwerk et al., 2022). This finding shows that web‐based eye tracking can be used successfully to assess children's goal‐based action predictions and is in line with previous studies reporting that moderated web‐based test sessions with children are comparable to in‐lab sessions (Chuey et al., 2021, 2022; Prein et al., 2022; Schidelko et al., 2021). Also, in line with previous remote studies in children, we found no statistically significant age effect (Chuey et al., 2022), suggesting that our web‐based eye‐tracking method may capture anticipatory looking behavior equally well among 18‐ to 27‐month‐olds.…”
Section: Discussionsupporting
confidence: 90%
“…We found that 18‐ to 27‐month‐olds’ goal‐based action predictions—reflected in above‐chance looking toward the location that matches the outcome of an agent's action goal—occurred in our remotely tested sample, replicating results obtained with in‐lab commercial eye‐tracking systems (Schuwerk et al., 2022). This finding shows that web‐based eye tracking can be used successfully to assess children's goal‐based action predictions and is in line with previous studies reporting that moderated web‐based test sessions with children are comparable to in‐lab sessions (Chuey et al., 2021, 2022; Prein et al., 2022; Schidelko et al., 2021). Also, in line with previous remote studies in children, we found no statistically significant age effect (Chuey et al., 2022), suggesting that our web‐based eye‐tracking method may capture anticipatory looking behavior equally well among 18‐ to 27‐month‐olds.…”
Section: Discussionsupporting
confidence: 90%
“…This finding shows that web-based eye tracking can be used successfully to assess children's goal-based action predictions. This finding is in line with previous studies reporting that moderated web-based test sessions with children are comparable to in-lab sessions (Chuey et al, 2021;Chuey et al, 2022;Prein et al, 2022;Schidelko et al, 2021). Also, in line with previous remote studies in children, we found no statistically significant age effect (Chuey et al, 2022), suggesting that our web-based eye-tracking method may capture anticipatory looking behavior equally well among 18-to 27-month-olds.…”
Section: Measuring Goal-based Action Prediction Using Remote Web-base...supporting
confidence: 92%
“…We adapted visuals and audio instructions specifically for each of the 17 communities. Previous work demonstrated excellent individual-level measurement properties for this task in a German sample 39 .…”
Section: Introductionmentioning
confidence: 85%